Interlinking journal and wiki publications through joint citation: Working examples from ZooKeys and Plazi on Species-ID - Lyubomir Penev; Gregor Hagedorn; Daniel Mietchen; Teodor Georgiev; Pavel Stoev; Guido Sautter; Donat Agosti; Andreas Plank; Michael Balke; Lars Hendrich; Terry Erwin (ZooKeys, 2011)
Scholarly publishing and citation practices have developed largely in the absence of versioned documents. The digital age requires new practices to combine the old and the new. We describe how the original published source and a versioned wiki page based on it can be reconciled and combined into a single citation reference. We illustrate the citation mechanism by way of practical examples focusing on journal and wiki publishing of taxon treatments. Specifically, we discuss mechanisms for permanent cross-linking between the static original publication and the dynamic, versioned wiki, as well as for automated export of journal content to the wiki, to reduce the workload on authors, for combining the journal and the wiki citation and for integrating it with the attribution of wiki contributors.